Border Disease In A Lamb: A Case Report - Akkaya, F; Evci, FZ; Küpeli, ZA; Kandemir, Ç; Taşkın, T; Koşum, N (Journal of the Hellenic Veterinary Medical Society, 2023)
In this case, it was aimed to report the clinical, hematological and pathological analysis results of a lamb born as infected with border disease virus (BDV). Severe central nervous system findings such as standing inability, continuous teeth grinding, muscle fasciculations in the head, ear and tail, hair loss around the eyes, lips and ears, abnormal appearance of the fleece, ataxia/rhythmic tremor and incoordination were detected in the case of lamb infected with BDV. The presence of BDV antibody and the levels of Triiodothyronine (T3) and Thyroxine (T4) were investigated in the serum samples for definite diagnosis. The tissue samples obtained from the brain and cerebellum were evaluated histopathologically and diagnosis of BDV was confirmed by necroscopic findings.